2022
DOI: 10.3390/w14040601
|View full text |Cite
|
Sign up to set email alerts
|

Recent Hydrological Droughts in Brazil and Their Impact on Hydropower Generation

Abstract: Brazil has endured the worst droughts in recorded history over the last decade, resulting in severe socioeconomic and environmental impacts. The country is heavily reliant on water resources, with 77.7% of water consumed for agriculture (irrigation and livestock), 9.7% for the industry, and 11.4% for human supply. Hydropower plants generate about 64% of all electricity consumed. The aim of this study was to improve the current state of knowledge regarding hydrological drought patterns in Brazil, hydrometeorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 81 publications
1
16
0
3
Order By: Relevance
“…Overall, 294 months presented SSI values classified as drought or abnormally dry, of which 51.7% occurred in the last third of the period (1996-2018), behavior also observed in other studies of hydrological drought in Brazil [65,71,73]. Consequently, this period from 1996 to 2018 displayed the lowest number of months with SSI ≥ 0.5, only 7.9% of the total.…”
Section: Hydrological Retrospective (Hr) and Historical Droughtssupporting
confidence: 80%
See 2 more Smart Citations
“…Overall, 294 months presented SSI values classified as drought or abnormally dry, of which 51.7% occurred in the last third of the period (1996-2018), behavior also observed in other studies of hydrological drought in Brazil [65,71,73]. Consequently, this period from 1996 to 2018 displayed the lowest number of months with SSI ≥ 0.5, only 7.9% of the total.…”
Section: Hydrological Retrospective (Hr) and Historical Droughtssupporting
confidence: 80%
“…In 2001, a severe drought hit a large part of the Southeastern Brazilian region, resulting in a national energy crisis due to the reduction in the reservoir level of hydropower plants [72]. The drought of the last decade was one of the most severe in recent years in several basins in Brazil, causing impacts on agricultural production, hydropower generation, and over the environment [28,65,68,73]. From 2012 to 2016, 33.4 million people were affected by the droughts in Brazil, with estimated damage of BRL 104 billion (approximately USD 20 billion) [69].…”
Section: Hydrological Retrospective (Hr) and Historical Droughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been caused by a variety of climatological factors that led to lower rainfall and higher PET (both trends also detected in this study), such as, changes in rainfall seasonality or lack of extremely high rainfall events. In a drought indicators analysis in Brazil [61], the authors found that the last decade (2011-2021) recorded the highest recurrence of severe droughts since 1981. The authors also suggest that droughts are more intense and frequent due to the compound effect of decreased precipitation and increased in temperature in a possible global warming scenario.…”
Section: Trends In Climate Variablesmentioning
confidence: 99%
“…The authors also suggest that droughts are more intense and frequent due to the compound effect of decreased precipitation and increased in temperature in a possible global warming scenario. The decreased precipitation and increased surface temperature result in the increased evapotranspiration and decreased soil moisture, leading to negative feedback processes that exacerbate drought events [61]. In a monthly precipitation assessment from 1961 to 2011 in Southeastern Brazil, non-significant trends were detected, but significant positive trends in mean temperature, as well as in PET for all months of that period were detected [48].…”
Section: Trends In Climate Variablesmentioning
confidence: 99%